2003
DOI: 10.1242/dev.00474
|View full text |Cite
|
Sign up to set email alerts
|

Tbx5 and Tbx4 trigger limb initiation through activation of the Wnt/Fgf signaling cascade

Abstract: A tight loop between members of the fibroblast growth factor and the Wnt families plays a key role in the initiation of vertebrate limb development. We show for the first time that Tbx5 and Tbx4 are directly involved in this process. When dominant-negative forms of these Tbx genes were misexpressed in the chick prospective limb fields, a limbless phenotype arose with repression of both Wnt and Fgf genes By contrast, when Tbx5 and Tbx4 were misexpressed in the flank, an additional wing-like and an additional le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
177
0
2

Year Published

2003
2003
2013
2013

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 156 publications
(185 citation statements)
references
References 48 publications
(68 reference statements)
4
177
0
2
Order By: Relevance
“…In support of these conclusions, in the chick, dominant-negative forms of Tbx5 misexpressed in the limb led to the absence of Wnt2b and Fgf10 expression in the prospective wing region (Takeuchi et al, 2003). In addition, misexpression of a dominant-negative form of Lef1 initially had no effect on Tbx5 expression (Takeuchi et al, 2003). These observations suggest that Tbx5 acts upstream of Wnt signalling (Agarwal et al, 2003;Takeuchi et al, 2003), although contradictory data in chick (Ng et al, 2002) indicates that this may have to be confirmed.…”
Section: A Genetic Hierarchy In Limb Initiation and Outgrowthmentioning
confidence: 65%
See 3 more Smart Citations
“…In support of these conclusions, in the chick, dominant-negative forms of Tbx5 misexpressed in the limb led to the absence of Wnt2b and Fgf10 expression in the prospective wing region (Takeuchi et al, 2003). In addition, misexpression of a dominant-negative form of Lef1 initially had no effect on Tbx5 expression (Takeuchi et al, 2003). These observations suggest that Tbx5 acts upstream of Wnt signalling (Agarwal et al, 2003;Takeuchi et al, 2003), although contradictory data in chick (Ng et al, 2002) indicates that this may have to be confirmed.…”
Section: A Genetic Hierarchy In Limb Initiation and Outgrowthmentioning
confidence: 65%
“…These results indicate that, in the mouse, Tbx5 acts upstream of Wnt signalling in the forelimb field, and that Wnt signalling, via β-catenin, Lef1 and Tcf1, is required to maintain normal levels of Fgf10 expression. In support of these conclusions, in the chick, dominant-negative forms of Tbx5 misexpressed in the limb led to the absence of Wnt2b and Fgf10 expression in the prospective wing region (Takeuchi et al, 2003). In addition, misexpression of a dominant-negative form of Lef1 initially had no effect on Tbx5 expression (Takeuchi et al, 2003).…”
Section: A Genetic Hierarchy In Limb Initiation and Outgrowthmentioning
confidence: 83%
See 2 more Smart Citations
“…An asterisk indicates the ablated side. for forelimb bud initiation (Ng et al, 2002;Takeuchi et al, 2003;Rallis et al, 2003;Hasson et al, 2007). Tbx5 is not expressed in the LPM before stage 13 in the chick embryo (Saito et al, 2002), and the LPM fate for forelimb-flank-hindlimb regionalization can be altered up to stage 13 (Saito et al, 2002(Saito et al, , 2006.…”
Section: Developmental Dynamicsmentioning
confidence: 99%